Frizioni urbane, progetti e perifericità divergenti. Dinamiche antropologiche del “modello orientale romano” - Pompeo, Francesco (Antropologia Pubblica, 2025)
This paper is the first elaboration and evaluation of a long-term ethnographic work. It represents the summation of two territorial intervention experiences, two action research projects in the former Eastern Roman periphery (2009-2011/ 2017-2022), the Casilino-Prenestino, which administratively the V Municipality, i.e. almost a municipality of 240,000 inhabitants. These limits have manifested themselves in various local crises: in the context of the difficult political-administrative transition of the post-Mafia capital, in the call for “security” as in the case of the “mosque crisis” (2017-2018) and the subsequent recurrent alarmist representations of an already structural migratory presence. While the most advanced response strategies are still those that work on participation and the implementation of shared governance, the research has shown that a participation policy based only on rhetorical and ritual evocation, but lacking analytical depth and reflexivity, has many conceptual blind spots that local government struggles to take into account. In fact, the process analysis highlighted the friction between the recognition of the actors of the so-called “civil society” (stakeholders), where they come into play together with the competence, the experience of relations with local authorities, as opposed to the ideologically claimed anonymity of the voice of the “citizens”.